Characterization and Molecular Identification of Lipolytic-bacterial Isolates Forming Biofilm on Polyethylene Plastic - Ariyanti, Olivia Puja; Agustina, Putri; Anif, Sofyan; Seno, Hernandito Aryo; Hardianto, Alden Ganendra Madhava Priya; Mandiri, Listy Hasti; Zulperi, Dzarifah; Jamil, Nazia; Rahayu, Triastuti; Sidiq, Yasir (Universitas Negeri Surabaya, 2025)
Polyethylene (PE) plastic is one of the most widely used for multiple purposes and leading the environmental problems. Lipolytic bacteria are promising agents to reduce the plastic waste. The dry weight of PE plastic was reduced by 33 % in the Winogradsky's column after 45 days of incubation. However, the lipolytic bacteria responsible for those reduction was unknown. This study aimed to characterize and identify the potential lipolytic bacterial isolates forming biofilm on polyethylene PE plastics. Samples of lipolytic bacterial isolates were screened on tributyrin selective media based on the formed clear zone. Moreover, the 16S rRNA genes of the two most potential lipolytic bacterial isolates were amplified. Then, the amplicons of the 16S rRNA gene were sequenced. This study found two potential lipolytic bacteria isolates, AB A-2 and AB M-3, which had the characteristics of round colonies, wavy edges, convex surfaces, and milky white color. The two isolates are gram-positive and have the shape of Coccobacillus cells. The molecular identification showed that AB A-2 isolate was Bacillus sp., while AB M-3 isolate was Bacillus amyloliquefaciens. This finding contributes to novel bacterial isolates that potentially overcoming the plastic waste problem.